2012
DOI: 10.1002/14651858.cd006260.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate start of hormonal contraceptives for contraception

Abstract: Analysis 4.1. Comparison 4 Immediate ring (etonogestrel 120 µg + EE 15 µg) versus immediate COC (NGM 180/215/250 µg + EE 30 µg), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Although safe and acceptable, there is minimal evidence that immediate initiation of OCPs or other methods of contraception reduces unintended pregnancy or increases long-term continuation. 36,37 Choice of pill regimen A number of OCP regimens are currently available for provision, including progestin-only versus combined oral contraceptives containing both estrogen and progestin, monophasic (no variation in hormone dose throughout the cycle) versus multiphasic (hormone dose varies throughout the cycle), and monthly cycle (withdrawal bleeding once every 28 days) versus extended cycle (withdrawal bleeding once every 84 days) versus continuous cycle (no withdrawal bleeding). A systematic review found evidence that discontinuation rates were higher with progestin-only pills than with combined OCPs, acknowledging the limitations of this evidence base.…”
mentioning
confidence: 99%
“…Although safe and acceptable, there is minimal evidence that immediate initiation of OCPs or other methods of contraception reduces unintended pregnancy or increases long-term continuation. 36,37 Choice of pill regimen A number of OCP regimens are currently available for provision, including progestin-only versus combined oral contraceptives containing both estrogen and progestin, monophasic (no variation in hormone dose throughout the cycle) versus multiphasic (hormone dose varies throughout the cycle), and monthly cycle (withdrawal bleeding once every 28 days) versus extended cycle (withdrawal bleeding once every 84 days) versus continuous cycle (no withdrawal bleeding). A systematic review found evidence that discontinuation rates were higher with progestin-only pills than with combined OCPs, acknowledging the limitations of this evidence base.…”
mentioning
confidence: 99%
“…8 Although it makes intuitive sense that starting contraception as soon as possible should decrease the risk of pregnancy for women, data have not consistently shown that the overall short-term or long-term method effectiveness is changed by timing of method initiation. 9 Specifically, for Cu-IUDs and LNG-IUDs, a systematic review did not suggest differences in continuation, expulsion, removal, or pregnancy rates when the devices are inserted at different times of the menstrual cycle. 10 Studies have examined the quick start method for CHCs, where a woman starts her contraceptive method either on the same day or shortly after her clinic visit, compared with the conventional start method, where the woman starts contraception with her next menses.…”
Section: Contraceptive Methods Initiationmentioning
confidence: 97%
“…All of the counselling sessions were performed by one of three gynaecologists (IK, MB, OK). Cochrane reviews and WHO guidance about contraception were used when needed [14][15][16][17][18]. All of the recommendations were at the basis of free-choice.…”
Section: Methodsmentioning
confidence: 99%